2019
DOI: 10.22159/ajpcr.2019.v12i18.33988
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of Vitamin D Deficiency Among the United Arab Emirates Population

Abstract: Objectives: The purpose of this study is to assess the Vitamin D deficiency awareness and perceptions between the United Arab Emirates (UAE) population. Methods: A cross-sectional study was done among the population of two emirates at the UAE: Abu Dhabi and Sharjah. Results: Overall, 434 participants completed the survey. Majority of people were aware of phenomenon of Vitamin D deficiency, but only 21.4% of them knew that sunlight is considered the main source of Vitamin D. Moreover, less than half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
2
10
1
1
Order By: Relevance
“…Our results also highlight the low rate of vitamin D testing among Emirati and International undergraduate female students; as only half of our sample reported ever getting tested. These results are in line with the ones recently reported in the UAE by Ibrahim and Al-Tameemi (2019) among adults in Abu Dhabi and Sharjah, where less than half of participants reported checking their blood Vitamin D blood regularly, and among adults in Al Ain, where only 43.4% of the participants reported that they were tested for vitamin D, and by Salmanpour et al (2016) in Sharjah. This finding is also common among undergraduate students elsewhere; Tariq et al (2020) reported that only 27.7% of undergraduate female students in Pakistan ever tested for vitamin D.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results also highlight the low rate of vitamin D testing among Emirati and International undergraduate female students; as only half of our sample reported ever getting tested. These results are in line with the ones recently reported in the UAE by Ibrahim and Al-Tameemi (2019) among adults in Abu Dhabi and Sharjah, where less than half of participants reported checking their blood Vitamin D blood regularly, and among adults in Al Ain, where only 43.4% of the participants reported that they were tested for vitamin D, and by Salmanpour et al (2016) in Sharjah. This finding is also common among undergraduate students elsewhere; Tariq et al (2020) reported that only 27.7% of undergraduate female students in Pakistan ever tested for vitamin D.…”
Section: Discussionsupporting
confidence: 92%
“…Our results add to the large body of evidence showing the poor knowledge about vitamin D, its health implications and sources among the general population and specifically undergraduate students around the world, in the Gulf region and the UAE (Janda et al, 2010;Babelghaith et al, 2017;Ibrahim and Al-Tameemi, 2019;Tariq et al, 2020). A recent study among adults in Abu Dhabi and Sharjah showed that only 21% of the participants knew that sunlight is the main source of Vitamin D (Ibrahim and Al-Tameemi, 2019). Similarly, a large study among university students in Canada (Boland et al, 2015) reported poor knowledge on vitamin D sources (26%), factors affecting its level (23%), its health effects (37%) and the recommended vitamin D intake (8%).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…According to many studies, a region such as the Middle East and Northern Africa (MENA), with a long sunny day duration, has recorded a very high incidence of VDD. These include over 90% of the population residing in the United Arab Emirates [9,14,15], around 80% of Saudis with different age groups [16,17], data from Iraq [8,13,[18][19][20][21], Qatar [22], and Jordan [23,24]. Similarly, deficiency is also prevalent among the American [1,4], Chines [25], Indian [26][27][28], British [5], and Norwegian [10] populations, among others.…”
Section: Introductionmentioning
confidence: 99%